Basic skills: the new paradigm curriculum in Europe - Luis Toribio Briñas (FahrenHouse, 2010)
The social, economic and cultural occurring in European Union, draw a scenario that raises the question about what are the basic skills to be acquired by citizens in the knowledge society and, on that basis, there is the need to rethink the education and training systems in key curriculum. Then arise Basic Skills, whose defining characteristics involve substantial implications in the design and curriculum development from the organizational framework curriculum to the Curriculum and Classroom Settings. Understand and correctly interpret this new framework is the great challenge we now face.